The Role Of The Teacher In Training The Independence Of Children BDR Period In Siloam Christian Kindergarten - Engelbertus Nggalu Bali; Martina Roslin; Irul Khotijah (Early Childhood Education Development and Studies (ECEDS), 2022)
The purpose of the study is to find out an overview of the role of teachers in training the independence of children aged 5-6 years during learning from home at Siloam Kota Baru Christian Kindergarten Kupang. The research method used in this research is qualitative research. The data collection techniques used in this study are interviews, observations and documentation. Data analysis used through steps in the form of data reduction, data presentation, verification or conclusion. The findings of this study are that the role of teachers in training children's independence by providing facilities to children, motivating children in forming child independence, making learning resources for children and observing all children's activities. The conclusion of this study is that learning strategies in schools carried out by teachers or educators have a great influence in increasing early childhood independence, therefore good teachers should need to increase their creativity in better learning strategies. This study provides input for the next researchers to conduct follow-up research on increasing independence that is more appropriate for children through certain learning strategies.